Phylogenetics of Gratioleae (Plantaginaceae): paraphyly of Stemodia and its implications for generic circumscriptions, with insights from floral evolution - Scatigna, André Vito (2022)
Gratioleae are the most species-rich tribe of Plantaginaceae in the tropics, spanning c. 30 genera and > 300 species, with a wide range of morphological variation and ecological strategies. As a first effort towards a phylogenetic classification of Gratioleae we generated a new phylogenetic hypothesis with improved taxa sampling, based on one nuclear and three plastid markers, using maximum parsimony and Bayesian inference approaches, and performed ancestral state reconstructions of ten morphological characters of flowers. The paraphyly of Stemodia s.l. was corroborated with members being retrieved in four clades; Bacopa, Conobea, Leucospora and Schistophragma are non-monophyletic. As actions towards recognizing only monophyletic genera in Gratioleae, we propose Stemodia s.s. as a monophyletic and morphological cohesive group, describe Umbraria as a new genus to accommodate two species segregated from Stemodia, transfer Stemodia vandelliodes to Darcya, merge Conobea with Bacopa and re-establish the names Chodaphyton ericifolium and Geochorda glechomoides. Traits used to define Stemodia s.l. are plesiomorphic in the tribe; the flower type (composed of seven floral characters) constitutes a good diagnostic set of traits for almost all genera in the tribe. Our study sheds light on the urgent need to reassess generic circumscriptions towards a unified classification in Gratioleae.